Modal interactions in shallow arches - Pedro Leal Ribeiro (2004)
Forced non-linear vibrations of shallow arches and straight beams are analysed. Thespatial model implemented uses a p-version finite element, where first-order sheardeformation is considered and the non-linearity is of the geometrical type. Theanalyses are carried out in the time domain by the shooting and Newmarksmethods. Interesting coupled-mode periodic vibrations are found.